Corrosion Rate Analysis of Steam Boiler Superheater: Analisa Laju Korosi Superheater Ketel Uap - Wibisono , Satria Agung; Fahruddin, A’rasy (Procedia of Engineering and Life Science, 2024)
Superheaters play an important role in converting saturated steam to the point of superheating. The condition of the superheater needs to be considered, if there is rust it will reduce the performance of the superheater in heating steam to the point of superheat. Rust / corrosion is the enemy of dangerous metals. Corrosion is defined as a deterioration in the quality of metals due to electrochemical reactions with their environment In corrosion events, metals undergo oxidation, while oxygen (air) undergoes reduction. The corrosion event itself is an electrochemical process, which is a process (change / chemical reaction) that involves electricity. Certain parts of the metal act as the negative pole (negative electrode, anode), while the other part acts as the positive pole (positive electrode, cathode). Electrons flow from the anode to the cathode, resulting in corrosion. By calculating the corrosion rate of superheaters with material A-213 T22 can be a consideration for using materials that are more resistant to rust or become a consideration in estimating repair time.